2007
DOI: 10.1080/15459620701223884
|View full text |Cite
|
Sign up to set email alerts
|

Metalworking Fluid Mist—Strategies to Reduce Exposure: A Comparison of New and Old Transmission Case Transfer Lines

Abstract: Three studies were performed to assess the effectiveness of various techniques to control metalworking fluid (MWF) mist. The studies consisted of a detailed main study that determined the effect of degree of enclosure on personal exposures and area concentrations of MWF mist on two machining transfer lines. One ancillary study was conducted to determine the effect of shutting off MWF delivery during down time; the second ancillary study investigated the effectiveness of improved retrofitted enclosure. In the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Originally equipped machines (OEMs) were reported to be associated with significantly lower exposure levels than retrofitted enclosures or machines with few or no enclosures (median 5 0.21 versus 0.45 and 0.48 mg m À3 , respectively, P , 0.05) (Hands et al, 1996). This finding was supported by studies reporting differences before and after upgrades (GM 5 2.24 versus 0.19 mg m À3 , respectively, P , 0.0001), on an old versus new transfer line (0.49 versus 0.26 mg m À3 , respectively, P 5 0.003) (Sheehan and Hands, 2007) and on machines using old versus new technology (Dasch et al, 2005). Another study found no statistically significant effect of splash guards on exposure levels (Piacitelli et al, 2001).…”
Section: Summary Of Determinants From the Literature Reviewmentioning
confidence: 61%
See 1 more Smart Citation
“…Originally equipped machines (OEMs) were reported to be associated with significantly lower exposure levels than retrofitted enclosures or machines with few or no enclosures (median 5 0.21 versus 0.45 and 0.48 mg m À3 , respectively, P , 0.05) (Hands et al, 1996). This finding was supported by studies reporting differences before and after upgrades (GM 5 2.24 versus 0.19 mg m À3 , respectively, P , 0.0001), on an old versus new transfer line (0.49 versus 0.26 mg m À3 , respectively, P 5 0.003) (Sheehan and Hands, 2007) and on machines using old versus new technology (Dasch et al, 2005). Another study found no statistically significant effect of splash guards on exposure levels (Piacitelli et al, 2001).…”
Section: Summary Of Determinants From the Literature Reviewmentioning
confidence: 61%
“…Thus, the technology was more effective for larger particles than for smaller particles (Dasch et al, 2005). Although an effect was reported for various types of engineering controls on total aerosol exposure levels (Hands et al, 1996;Piacitelli et al, 2001;Dasch et al, 2005;Sheehan and Hands, 2007), the number of aerosol exposure measurements with same (or similar) engineering control type in these studies was insufficient to allow us to conduct a meaningful analysis.…”
Section: Discussionmentioning
confidence: 94%
“…Many of these report prevailing exposures less than 0.5 mg/M 3 , frequently at 0.25 mg/M 3 and below Thornburg, 2000;Yacher et al, 2000;Piacitelli et al, 2001;Rosenthal and Yeagy, 2001;Dasch et al, 2002;Leith et al, 2003;Stear, 2003;Ross et al, 2004;Raynor et al, 2005]. A recent study directly addressed the feasibility and practicality of retrofitting equipment for controlling exposures generated by existing high production, linear transfer lines [Sheehan and Hands, 2007].…”
Section: Exposure Measurement and Controlmentioning
confidence: 99%
“…The control of the occupational exposures and health effects and exposure assessment has been intensively studied [3][4][5][6][7]. Moreover, several organizations such as US Occupational Safety and Health Administration, US National Institute for Occupational Safety and Health, and US Environmental Protection Agency are very active in promoting health and safety guidance through substantial standards related to occupational exposure to metalworking fluids and aerosols.…”
Section: Process Level Considerationsmentioning
confidence: 99%